Interactions between Phytochemical Components of Sutherlandia Frutescens and the Antiretroviral, Atazanavir In Vitro: Implications for Absorption and Metabolism - Adrienne C Müller; Srinivas Patnala; Olena Kis; Reina Bendayan; Isadore Kanfer (Frontiers Media S.A., 2012)
Purpose. African traditional medicinal plants, such as Sutherlandia frutescens have the potential to interact pharmacokinetically with the protease inhibitor class of antiretrovirals, thereby impacting on their safety and efficacy. The effects of extracts and phytochemical components of Sutherlandia frutescens, on the in vitro absorption and metabolism of the protease inhibitor, atazanavir were thus investigated. Methods. Aqueous and methanolic extracts of Sutherlandia frutescens were prepared by freeze-drying of hot water and methanol decoctions of Sutherlandia frutescens plant material respectively, whilst crude triterpenoid glycoside and flavonol glycoside fractions were isolated by solvent extraction and subsequent column chromatography. Atazanavir was quantitated in the absence or presence of these compounds as well as commercially available purported constituents of Sutherlandia frutescens, namely, L-canavanine, L-GABA and D-pinitol, after a one hour co-incubation in Caco-2 cell monolayers and human liver microsomes. Results. The triterpenoid and flavonol glycoside fractions were found to be present in the aqueous and methanolic extracts of Sutherlandia frutescens and were shown to contain the sutherlandiosides and sutherlandins known to be present in Sutherlandia frutescens. The aqueous extract and D-pinitol significantly reduced atazanavir accumulation by Caco-2 cells, implying a decrease in atazanavir absorption, whilst the opposite was true for the triterpenoid glycoside fraction. Both the aqueous and methanolic extracts inhibited atazanavir metabolism in human liver microsomes, whilst enhanced atazanavir metabolism was exhibited by the triterpenoid glycoside fraction. Conclusions. The extracts and phytochemical components of Sutherlandia frutescens influenced the accumulation of atazanavir by Caco-2 cells and also affected ATV metabolism in human liver microsomes. These interactions may have important implications on the absorption and metabolism and thus the overall oral bioavailability of atazanavir. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.